Future Scenarios Modeling of Urban Stormwater Management Response to Impacts of Climate Change and Urbanization. Issue 10 (14th September 2017) - Wang, Mo; Zhang, Dong Q.; Su, Jin; Trzcinski, Antoine P.; Dong, Jian W.; Tan, Soon K.
Abstract : Future scenarios modeling is used to investigate the effectiveness of the urban stormwater infrastructure and its response to potential future changes. The changes of urban stormwater, both in‐flow quantity and water quality, in response to climate change and urbanization are examined and tested in two highly developed urban catchments using the US Environmental Protection Agency's Storm Water Management Model. Similar responses are observed in the two catchments, despite their differences in size and land use. Flow quantity and water quality appears to be more sensitive to urbanization factors than to climatic change. With respect to factors attributable to urbanization, urban intensification (land use plus population density) has more of an effect than land‐use changes alone. Low‐impact development, as a key adaptation measure, could be effective in mitigating the adverse impacts of future changes on urban stormwater. The methodology developed in this study may be useful for urban stormwater planning and testing such plans against future urbanization and climate change scenarios. Abstract : Future‐scenarios modeling is used to investigate the performance of urban stormwater management in two highly developed urban catchments in response to potential future changes. Flow quantity and water quality appeared to be more sensitive to urbanization, especially urban intensification. In addition, low‐impact development could be effective in mitigating the adverse impacts of future changes on urban stormwater.